Kritik Terhadap Penggunaan Metode Penafsiran Literal dalam Tafsir Al-Qur’an - Sani, Azwar (STAI Darul Kamal NW Kembang Kerang, 2024)
This research aims to criticize the use of literal interpretation methods in the interpretation of the Quran and offer contextual interpretation as an alternative method of interpretation. The study analyzed the history of the use of literal interpretation methods in the interpretation of the Quran, the characteristics of literal interpretation methods, the weaknesses of literal interpretation methods, and the impacts of using literal interpretation methods. The method used in this study was qualitative with a literature study approach. Data was collected through a literature study of books, journals, and related articles. Then, data analysis was conducted using a qualitative descriptive analysis method. The results of the study show that the use of literal interpretation methods in the interpretation of the Quran still lacks attention to the historical and social context when writing verses, and produces a rigid and limited understanding of the Quranic text. The excessive use of literal interpretation methods can also lead to conflicts among Muslims. The impacts of using literal interpretation methods include producing a rigid understanding of religion, neglecting the development of times and the needs of Muslims, and not paying enough attention to social justice values in the Quran. As an alternative, contextual interpretation is offered as a method that pays more attention to the historical, social, and cultural context when writing verses in the Quran. In conclusion, this research shows that the use of literal interpretation methods in the interpretation of the Quran has many weaknesses and negative impacts, so it is necessary to consider using alternative methods such as contextual interpretation.